UXT at the crossroads of cell death, immunity and neurodegenerative diseases - Han, Pengzhe; Mo, Shaojian; Wang, Zhengwang; Xu, Jiale; Fu, Xifeng; Tian, Yanzhang (Frontiers in Oncology, 2023)
The ubiquitous expressed transcript (UXT) is a member of the prefoldin-like protein family. UXT modulates regulated cell death (RCD) such as apoptosis and autophagy mediated cell death through nuclear factor-κB (NF-κB), tumor necrosis factor-α (TNF-α), P53, P62, and methylation, and is involved in the regulation of cell metabolism, thereby affecting tumor progression. UXT also maintains immune homeostasis and reduces proteotoxicity in neuro-degenerative diseases through selective autophagy and molecular chaperones. Here, we review and further elucidate the mechanisms by which UXT affects the regulation of cell death, maintenance of immune homeostasis, and neurodegenerative diseases. We discussed the possibility that UXT is involved in the regulation of ferroptosis and immunogenic cell death. And the possibility of targeting UXT to be involved in improving cancer treatment outcomes by regulating cell death and immune surveillance.